COVID-19 vaccine information disorder in Chile: a quantitative analysis of fact-checked articles - Cruz, Alexis V.; Schulz, Vicente; Arriagada, Eduardo; Montero-Liberona, Claudia A.; Kalergis, Alexis M. (Frontiers in Public Health, 2025)
IntroductionPrevious studies have analyzed information disorder during the COVID-19 pandemic, focusing on common characteristics such as content formats, recurring themes, and information dissemination networks. However, in the Latin American region, there is still a gap in studying the specific characteristics of this phenomenon during the COVID-19 vaccination process, as in the Chilean case. Therefore, this study aims to identify the main characteristics of information disorder circulating in Chile during the COVID-19 vaccination process, considering key topics, actors, and media platforms involved.MethodsWe conducted a quantitative content analysis of a dataset of 140 fact-checking articles related to COVID-19 vaccination, sourced from MalaEspina and FastCheck, from March 2020 to December 2022.ResultsWe identified the primary characteristics of information disorders that circulated in Chile concerning the COVID-19 vaccination process. Our main findings indicated that information disorder focused on disinformation intended to cause harm through deception. The primary format used was visual and distributed across various platforms.Discussion and conclusionWe conclude that studying information disorder in specific topics, such as vaccination, is important to understand the phenomenon better and develop strategies to mitigate its impact on society.